2014
DOI: 10.1016/j.stemcr.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

3D Reconstitution of the Patterned Neural Tube from Embryonic Stem Cells

Abstract: SummaryInducing organogenesis in 3D culture is an important aspect of stem cell research. Anterior neural structures have been produced from large embryonic stem cell (ESC) aggregates, but the steps involved in patterning such complex structures have been ill defined, as embryoid bodies typically contained many cell types. Here we show that single mouse ESCs directly embedded in Matrigel or defined synthetic matrices under neural induction conditions can clonally form neuroepithelial cysts containing a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 47 publications
9
181
0
Order By: Relevance
“…To begin to understand how molecular signals and the extracellular microenvironment coordinate to form early structures of the central nervous system (CNS), we have begun to generate organoids with defining features of developing spinal cord (8). Our previous work with Matrigel has shown that single mouse ESCs could form apical-basal neuroepithelial cysts containing single lumens (8), and that retinoic acid (RA) could induce such cysts to yield patterning along a dorsal-ventral (DV) axis recalling the spatial organization found in the developing neural tube.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…To begin to understand how molecular signals and the extracellular microenvironment coordinate to form early structures of the central nervous system (CNS), we have begun to generate organoids with defining features of developing spinal cord (8). Our previous work with Matrigel has shown that single mouse ESCs could form apical-basal neuroepithelial cysts containing single lumens (8), and that retinoic acid (RA) could induce such cysts to yield patterning along a dorsal-ventral (DV) axis recalling the spatial organization found in the developing neural tube.…”
Section: Significancementioning
confidence: 99%
“…Our previous work with Matrigel has shown that single mouse ESCs could form apical-basal neuroepithelial cysts containing single lumens (8), and that retinoic acid (RA) could induce such cysts to yield patterning along a dorsal-ventral (DV) axis recalling the spatial organization found in the developing neural tube. Although some studies with synthetic PEG matrices have suggested that adhesion ligands play an important role in establishing apical-basal polarity in model systems of epithelial morphogenesis (18), it has remained unresolved which aspects of Matrigel contribute to this spatial organization, and in particular the role of extracellular microenvironment in establishing complex morphogenesis.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In theory, platforms that instruct R/C and D/V morphogenetic patterning of developing organoids by exogenous application of morphogen gradients will also be needed. However, recent work describing spontaneous D/V patterning in mouse ESC-derived cysts may indicate that this is not necessary [56]. Regardless, intimate integration of tissue engineering methodologies with organoid derivation protocols will be needed to advance towards instructed organoid morphogenesis and create next generation CNS in vitro models and potentially even organ transplants.…”
Section: Resultsmentioning
confidence: 99%
“…Using this system, neuroepithelial cysts could be reconstituted from mouse embryonic stem cells directly embedded in 3D culture. [199] Three different 3D cell culture systems were compared: (i) Matrigel, (ii) laminin/entactin, and (iii) synthetic PEG hydrogel. ECM proteins improved cyst-forming ability – although they were not required to generate lumen-containing neuroepithelial cysts in the 3D culture system.…”
Section: Designing Synthetic Matrices For Recapitulating the Extramentioning
confidence: 99%